Transformasi Pendidikan Islam di Era Digital: Isu, Tantangan, dan Peluang - Ari Rahmatullah Fauzi; Istikhori Istikhori; Muhamad Rafli (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study examines the transformation of Islamic education in the digital era, focusing on issues, challenges, and opportunities. The development of digital technology has brought significant changes in Islamic learning, including curriculum innovation, teacher competence, digital literacy, and the ethical use of technology. Using a qualitative literature review method, this article analyzes primary and secondary data from national and international journals to present a comprehensive discussion. The findings highlight that while digital transformation provides opportunities for broader access to knowledge, it also raises concerns about the digital divide, the role of teachers, and the maintenance of Islamic values. Furthermore, the increasing reliance on digital tools in education has intensified the need for teachers to adapt to new technologies and methodologies. The study concludes that strengthening digital literacy, professional teacher training, and appropriate policy support are crucial for optimizing Islamic education in the digital age. The findings stress the importance of balancing technological integration with the preservation of traditional Islamic values in educational practices.